Trends of Utilization Plants Resources among Santhal of Nepal - Baral, Mounta; Poudel, Pratik; Adhikari, Dipendra; Sangroula, Mohan (Damak Campus Journal, 2023)
An ethnobotanical survey was conducted in Gauradaha municipality of Jhapa, Nepal. The objectives of study were documentation of ethnobotanical practices of santhal tribes. Some common ethnobotanical methodologies and techniques were applied during the course of study. Altogether 30 households were surveyed. 56 peoples were participated among them 8 were informants of age ranged from 40 to 90 years. Total 88 varieties of plants were listed which are used for different purpose and these species were distributed among 76 genera of 49 families. The highly represented family was Poaceae (7 species), Solanaceae (6 species), Compositae (5 species). The remaining families comprise very few species of identified plants. Distribution of plants according to habit were reported, among them herbs (42%), shrubs (27%), trees (24%) and climbers (7%).The majority of the plant species were reported to be used for medicinal purpose (36%)followed by multiple used i.e. a plant used for different purpose (27%), vegetable(12%), fodder (6%), food (6%), ornamental (5%), religious (5%) and fruit (3%).Distribution of plants according to part used were reported i.e. leaf (30%), multiple part i.e. different parts of a plant used (17%), fruit (16%), whole part (10%), stem (9%), seed(6%), root (6%), flower (4%) and bark (2%) for various purpose. So, from this study it is clear that this tribe has good knowledge about the importance of plant available in the study area.